Strategi Pembelajaran Guru Pendidikan Agama Islam Dalam Menanamkan Nilai-Nilai Moderasi Beragama Untuk Menjaga Kerukunan Antar Umat Beragama Siswa Di SMA Negeri 1 Air Putih - Maulana, Agung; Barus, Jusua; Syahlan, Ali (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The research results show that SMA Negeri 1 Air Putih shows a strong commitment to the values ​​of religious moderation, with a main focus on tolerance, inclusivity and respect for differences in beliefs. This approach is reflected in the formal curriculum, extracurricular activities, and social activities that encourage interfaith dialogue. Based on the learning strategy implemented by the Islamic Religious Education (PAI) Teacher at SMA Negeri 1 Air Putih in instilling the values ​​of religious moderation, the following conclusions can be drawn, namely a Holistic Approach to Learning; Interactive Learning Methods; Involvement in Extracurricular Activities; Resource Use and Collaboration; School Support and Commitment. Overall, the learning strategies implemented by Islamic Education Teachers at SMA Negeri 1 Air Putih have proven their effectiveness in instilling the values ​​of religious moderation in students. With a comprehensive, interactive approach and involving many parties, PAI teachers have succeeded in helping students understand, appreciate and internalize attitudes of tolerance and respect for religious diversity in everyday life. This is not only relevant for the educational context in schools, but also equips students with the skills necessary to live harmoniously in a multicultural and multireligious society.